Compliant Mechanism Soft Robot Design and Peristaltic Movement Optimization Using Random Search. (12th April 2022) - Páramo-Carranza, L. A.; Lopez-González, A.; Tejada, Juan C.
Abstract : In this article, we use the concept of auxetic structures as inspiration for the design of a compliant mechanism that allows the integration of a soft robot whose movement is based on the peristaltic movements of invertebrates. The TPU mechanism allows for smooth movement of the robot using only two servo motors. To guarantee maximum displacement, a time and angle optimization procedure using photogrammetry and random search was carried out, allowing the advance distance of the soft robot to be maximized.